Development of Point-of-care Paper Based Strip for the Detection of Simple Antipyretic-analgesic Drugs - Kumar, GVSR Pavan; Rao, K Srinivasa (Indian Journal of Pharmacy Practice)
A paper-based strip was developed by the authors for the detection and quantitative determination of paracetamol in bulk and pharmaceutical formulations for point-of-care testing prior to the assay prescribed in the respective pharmacopeia. In the present paper, lab-on-chip technology was used for the assay of a simple NSAID drug paracetamol. The qualitative analysis of the drug on the strip was performed by using three different reagents such as sodium Meta vanadate (1%), potassium dichromate (0.01M), N-bromosuccinamide (1%). This method employs dissolution of the powdered sample of drug in distilled water, followed by placing the sample solution of the drug on the strip of paper which was previously impregnated with the reagent. Drug concentrations were quantified from color intensity images using a scanner in conjunction with image processing software MATLAB. Linear calibration curves were generated for the drug with each of the reagent. The results obtained were compared with standard methods such HPLC and found to be in accordance with standards. This technology provides qualitative analysis and a prior easy step before assay of the drug at appreciably reduced costs.
Keywords: Pharmaceutical formulations; Paracetamol; Point-of-care devices; Wax printing; MATLAB.